PERSAINGAN DALAM PENGELOLAAN OBJEK WISATA ALAM SUNGAI HIJAU DI DESA SALO KECAMATAN SALO KABUPATEN KAMPAR - Baref Fajri Adiagung Purnando; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sungai Hijau is one of the Natural Tourism Objects located in Salo Village, Salo District, Kampar Regency. Sungai Hijau is a small river with clear water and filled with small rocks along its base. Moss that grows in a number of small rocks and aquatic plants that grow on the banks of the river make this river more green. The Sungai Hijau Natural Tourism Object is divided into four tourist attraction locations, namely Sungai Hijau 1, 2, 3 and 4. The number of locations of the Sungai Hijau Natural Tourism Object resulted in competition among the owners of the Sungai Hijau Nature Tourism Object. The purpose of this study was to determine the forms of competition in the management of the Sungai Hijau Natural Tourism Object and the impact of competition on the management of the Sungai Hijau Natural Tourism. This study uses a qualitative approach with descriptive analysis. The selection of informants in this study was carried out with a purposive sampling technique that is taking data from informants based on certain criteria. These criteria are the owners of each of the Sungai Hijau Natural Tourism Objects who also participated in managing the Sungai Hijau Natural Tourism Object. Data collection techniques used in this study were interviews, observation, documentation. The results of this study state that the forms of competition in the management of the Sungai Hijau Natural Tourism Object include competition in terms of economy, culture and political. The impact of competition on the management of Sungai Hijau Natural Tourism is the occurrence of fair prices, increased managerial performance, more complete and diverse facilities, reducing income from each of the Sungai Hijau Natural Tourism Objects and causing disputesKeyword: Competition, The Sungai Hijau Natural Tourism Object